The Supply Management Handbook - Cavinato, Joseph L.; Flynn, Anna E.; Kauffman, Ralph G. (McGraw-Hill Education LLC., 2006)
For more than three decades, The Supply Management Handbook (formerly The Purchasing Handbook) has been vital for purchasing and supply professionals in every field and industry. This latest edition comprehensively updates and revises this classic to encompass the ongoing shift from simple purchasing to a new, more technology-based imperative--identifying and managing supply chain sources and strategies. Addressing every essential issue from outsourcing to total cost of ownership to negotiations and contract management, an international team of supply management experts offers the authoritative, practical coverage you need to survive and thrive in today's ever-changing supply management environment. - Publisher.